Evaluación formativa oportunidad en el proceso de enseñanza aprendizaje en el área de matemáticas en tiempos de pandemia (2021)
This research seeks to strengthen the formative evaluation processes in 3rd grade teachers in the area of mathematics at the Sagrado Corazón de Jesús Educational Institution in times of pandemic. Its methodology is qualitative, framed in the socio-critical paradigm, an action research design. The categories of this research are: Formative evaluation and the teaching of mathematics, in it the formative evaluation is retaken at a theoretical level as a process of continuous improvement, with an integral notion. Investigative tools such as the semi-structured interview, the focus group, discussion groups, participant observation, the documentary review and a series of trainings were used. With the application of the initial interview, results were reached such as the existence of traditional formative and evaluative processes; which are limited to qualifying and not sure the learning of the students, which merits a change in the evaluative methodology, in this case the formative type. The conclusion is reached that FDI should improve the quality of the educational service they offer, with formative evaluation being a bridge towards the establishment of new proposals; open and inclusive; that enhance academic processes. The design of pedagogical workshops set the standard, of how we can stimulate the thought or mental operations of the learner; that learns to solve problems and fundamentally be able to use what they have learned to analyze the reality of their context.